Software Summaries. - Hendrickson, Harvey S.; Carter, Jack L.; Steinbart, Paul J.; Greynolds, Elbert B. (The Accounting Review, 1986)
Reviews several books. "Spreadsheet Applications in Managerial Accounting," by Angelo E. Diantonia; "The Use of Microcomputers in Accounting," by Sam A. Hicks and Donald V. Saftner; "Using Microcomputers in Managerial Accounting," by George Hildebrand.